Deliberative Democracy: Affirmative Action Policy on the 30% Quota for Women in Parliament - Ummah, Siti Muslikhatul (Indonesian Academy of Social and Religious Research (IASRR), 2023)
This paper aims to determine the process of deliberative democracy in the use of affirmative action 30% quota for women as a starting point in increasing women's representation in parliament. This is because in gender equality in politics in Indonesia there is a large gap between the representation of women and men even after the policy is enacted. Through deliberative democracy, increasing women's representation can use policies made through discursive means in civil society. The method in this paper is a descriptive qualitative method using the author's analysis of book reviews and research with related themes. The results of this paper study the ratification of affirmative action policies in 2023 through various kinds of dialogue and rejection. Arguments for rejection include (1) equality is considered an individual quality, not a quota, (2) quotas are considered an obstacle, (3) psychological constraints on women, (4) gender construction against women. The rejection argument makes the affirmative action policy a massive debate in the public sphere which becomes the aspiration of women activists to fight for in the political system. Habermas' view states that a legal product will gain strong legitimacy if in the process of making it through debate and discussion in the public sphere.